PENDIDIKAN ISLAM DALAM RUMAH TANGGA MENURUT PEMIKIRAN ASY SYAIKH AL IMAM ABU MUHAMMAD DALAM KITAB QURROTUL ‘UYUN - Jani Sanjari; Ripa Putri Oktaviani (HASBUNA : Jurnal Pendidikan Islam, 2024)
This research is based on the fact that currently there is a lot of conflict in the household, causing many divisions in the family, even leading to divorce. This happens because they do not understand the procedures for forming a household according to Islamic instructions and many couples do not know the duties and responsibilities in forming a household. The aim of this research is to find out and increase insight into Islamic education in the household according to the thoughts of Ash Shaykh Al Imam Abu Muhammad in his book, namely the book Qurrotul 'Uyun. The author uses qualitative research procedures with content analysis research methods, and the primary source is the book Qurrotul 'Uyun. The research results show that Islamic education in the household covers many things about the Sakinah family. As described in the book Qurrotul 'Uyun, the Sakinah family is a family formed on a strong religious basis. In his daily behavior he is always guided by the instructions of Allah and His Messenger, thereby creating a religious climate within him. Meanwhile, efforts that can be made are: (1) Selective selection of a life partner (2) Maintaining family harmony (3) The principle of balance between the rights and obligations of husband and wife (4) The important role of sexuality for family happiness. It is hoped that future researchers will be able to dismantle more deeply the thoughts contained in the book Qurrotul 'Uyun, because this book explains Islamic education in the household.